Spontaneous Evisceration of Incisional Hernia with Strangulation of Small Bowel: A Life Threatening Complication - Nanduni Thalahitiyage; Sanjeevan Ravindrakumar; Janaka Nandasena; Arooran Krishnakumar; KirushanthanVeerasingam; Umesh Jayarajah; V. S. D. Rodrigo (Case Reports in Surgery)
Spontaneous evisceration of abdominal viscera is a rare complication of incisional hernia which could pose a serious threat to life if intervention is delayed. We report a case of a 62-year-old female with a history of curative resection for stage 1 endometrial adenocarcinoma 3 years ago, presenting with spontaneous evisceration of incisional hernia with strangulation of small bowel. Immediate resuscitation followed by emergency surgery was mandatory. During surgery, priority should be given to release the strangulation as soon as possible and the type of repair would depend on the viability of the bowel and the anatomy of the incisional hernia.